2007
DOI: 10.4049/jimmunol.179.12.8446
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Parasite-Encoded Arginase on the Outcome of Murine Cutaneous Leishmaniasis

Abstract: Classical activation of macrophages infected with Leishmania species results in expression and activation of inducible NO synthase (iNOS) leading to intracellular parasite killing. Macrophages can contrastingly undergo alternative activation with increased arginase activity, metabolism of arginine along the polyamine pathway, and consequent parasite survival. An active role for parasite-encoded arginase in host microbicidal responses has not previously been documented. To test the hypothesis that parasite-enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 51 publications
7
94
1
5
Order By: Relevance
“…As far as Leishmania arginase is concerned, the lack of this enzyme as in arg À/À L. major or in arg À/À L. mexicana showed impaired infectivity resulting in delayed onset of lesion development, attenuated pathology, and low parasite burden [22]. Results also suggest that parasite-encoded arginase of L. major subverts macrophage microbicidal activity by diverting arginine away from iNOS [23]. L-arginine depletion and arginase-1-induced polyamine production favors the growth of L. major, and parasite-encoded arginase seems to partially control parasite replication and disease manifestation in macrophages [22].…”
mentioning
confidence: 63%
“…As far as Leishmania arginase is concerned, the lack of this enzyme as in arg À/À L. major or in arg À/À L. mexicana showed impaired infectivity resulting in delayed onset of lesion development, attenuated pathology, and low parasite burden [22]. Results also suggest that parasite-encoded arginase of L. major subverts macrophage microbicidal activity by diverting arginine away from iNOS [23]. L-arginine depletion and arginase-1-induced polyamine production favors the growth of L. major, and parasite-encoded arginase seems to partially control parasite replication and disease manifestation in macrophages [22].…”
mentioning
confidence: 63%
“…Whether all of these enzymes are also essential for the amastigote to maintain an infection is less clear, because virulence data with knockout strains from several species have not offered a consistent conclusion. Parasite burdens and lesion sizes of mice infected with ⌬arg L. mexicana (23) or ⌬arg L. major (43,48) were only somewhat lower than those of mice infected with the corresponding wildtype line from which these mutants were derived. In contrast, parasite loads in mice infected with ⌬odc L. donovani (12) were dramatically reduced by many orders of magnitude compared to those in mice inoculated with the wild-type progenitor.…”
Section: Discussionmentioning
confidence: 92%
“…The genes encoding all four enzymes have been cloned, and conditionally lethal gene knockouts have been created in L. mexicana and L. major (⌬arg mutant only) (23,43,48,52) and in L. donovani (⌬odc, ⌬spdsyn, and ⌬adometdc mutants) (12,34,50,51) via double-targeted gene replacement. Growth studies with the mutant promastigotes revealed that each knockout was auxotrophic for polyamines as a consequence of the gene deletion events and that this nutritional deficiency could be circumvented by propagation in medium supplemented with an appropriate source of polyamine or polyamine precursor.…”
mentioning
confidence: 99%
“…The L. mexicana knockout for arginase infection led to an enhanced Th1 response associated to an INF-γ upregulation as well. Taken together, these responses led to a significant growth attenuation of the parasite in mice (Gaur et al, 2007). Considering the importance of the cellular signaling pathways involving the host cells and parasites of the Leishmania genus there are few studies in the literature connecting the importance of the parasite arginase inhibition and macrophage NO production.…”
Section: Resultsmentioning
confidence: 99%